Important factors to influence the coverage of drinking water - Purbasari, Heppy; Bawono, Andy Dwi Bayu; Wahyudi, Luki Eko (Journal of Economics Research and Policy Studies, 2023)
This research is motivated by the phenomenon where the coverage of drinking water in Java in 2019-2020 is still below the standard set by the sustainable development goals. Out of Java's 226 districts/cities, only half have drinking water coverage above the average. This research aims to determine factors influencing drinking water coverage in districts/cities in Java. The data used in this study are secondary data obtained from the Central Statistics Agency and the Directorate General of Finance using a quantitative approach—the multiple linear regression model of this study. The method used in this study is multiple linear regression. The research findings indicate that infrastructure expenditure, the number of poor populations, and DAU significantly influence drinking water coverage, while DAK does not significantly influence drinking water coverage.